The ecology of medical care in Shanghai - Xuechen Xiong; Xiaolin Cao; Li Luo (BMC, 2021)
Abstract Background To better understand the distribution and consumption patterns of resources in different ethnic groups and at different levels of economic development, this paper chose to describe the healthcare seeking behavior in Shanghai. Methods The data are from the Sixth Health Service Survey of Shanghai, which encompasses 23,198 permanent residents. Descriptive analyses were conducted to estimate the number of patients who reported health-related symptoms and healthcare-seeking behaviors per 1,000 residents. Logistic regression analyses were conducted to examine differences in reporting health-related symptoms and healthcare-seeking behaviors by age, gender and area of residence. Results This paper have mapped the ecology of healthcare in Shanghai in 2018. Of 1000 individuals considered during a 1-month period, 444 reported sickness, 433 received treatment, 288 went to medical institutions, 195 went to primary medical institutions, 86 took a self-healing approach, 26 received TCM services, 7 were hospitalized, and 3 underwent surgery. Conclusions Age is a risk factor leading to disease, medical treatment, self-medication, medical institution visits, TCM service, hospitalization and surgery. But age is a protective factor in the use of primary health care services. By gender, the number of people receiving medical services was similar, but women were statistically more likely to have surgery. As the income level increased, the number of patients and people receiving medical services showed a decreasing trend. Compared with the local population, the probability of non-local people visiting medical institutions was lower and statistically significant. Compared with the people who had health insurance, fewer uninsured people reported sickness and utilized healthcare services.